Specific assessment exercises based on visual sensory modeling and its effect on some biomechanical indicator spiking skill on volleyball - Alsaeed, Riyadh; Kazem, Hussein Ali; Kamel, Saif Shaker; Jawad, Wael kassim (مجلة دراسات وبحوث التربية الرياضية, 2024)
The spiking skill is one of the types of volleyball skills the mission and which leads The technical aspect plays an important role and this is what makes the player who studies the details of this skill work to confront incorrect performance by relying on additional visual sensory modeling using modern qualitative analysis techniques in a different way directly to identify some basic faulty biomechanical indicators for the stages of technical performance of the spiking skill and the extent of their need for change according to some exercises which contributes to increasing and supporting the motor path of the skill, which helps learners perform the skill successfully, therefore, the researchers used the experimental method using a one-group experimental design appropriate to the nature of the study, the research sample was chosen by the researchers intentionally. The juniors of the Iraqi national volleyball team, where (7) players were selected who are proficient in the skill of striking. Where the researchers were keen to implement specific evaluative exercises in terms of sensory modeling using different tools with a purpose development Some biomechanical indicators developing the muscular strength of a sample of individuals the study in a period of (8) weeks and included (24) training units, (3) units per week, the conclusions, The most important study was that sorting out the mechanical errors related to performance and witnessing them by each learner instilled in themselves the motivation to reach ideal performance according to the corrective exercises that aimed to develop the absolute strength of each of the muscular moments